(untitled) (International Journal of Health, Animal Science and Food Safety, 2014)
Zinc (Zn) salts are often used as nutritional additives in order to promote gut health. The aim of the present study was to assess the effect of two widely used additives in feedstuff, on the intestinal epithelium. In particular, the effect of zinc oxide (ZnO) and zinc chloride (ZnCl2) was investigated in human (INT-407) and porcine (IPI-2I) cell line models. The effect of Zn sources on IPI-21 and INT-407 cell lines was evaluated by a colorimetric viability test using an incubation period of 3 and 24 hours under serum-free conditions. INT407 and IPI-2I showed to be a suitable model of the intestine and a simple tool to investigate the role of Zn supplements. INT407 showed to be the most sensible model to Zn supplements considered, whereas IPI-2I were more resistant. The results of this study contribute to determine the role of zinc in human and swine intestinal epithelium. However, further in vivo experiments may be done to clarify the contribution of Zn supplements in gut health and to improve Zn supplementation in animal feed and in human formulations.